Persistent stunting in middle childhood : the case of Andhra Pradesh using longitudinal data - Himaz, R (2009)
This article looks at what observable characteristics influence a child being persistently stunted, moving from being stunted or moving into being stunted in middle childhood, between 7 and 12, using longitudinal data for Andhra Pradesh. It finds the key factors that help a child move out of being stunted are mother’s education and coming from the more prosperous region of Coastal Andhra. In contrast, the key factors that pushed a child into being stunted were the child being a girl and being a younger sibling. We also find that children who moved out of being stunted consume a diet higher in protein and micronutrients than others. The article suggests that even if a child starts middle childhood with significant shortfalls in height accrued from earlier on in life, nutritional interventions and adult female education may have a positive impact on linear growth and perhaps mitigate consequences of early age stunting.